A new dawn for the naming of fungi: impacts of decisions made in Melbourne in July 2011 on the future publication and regulation of fungal names - D.L. Hawksworth (IMA Fungus)
A personal synopsis of the decisions made at the Nomenclature Section meeting of the International Botanical Congress in Melbourne in July 2011 is provided, with an emphasis on those which will affect the working practices of, or will otherwise be of interest to, mycologists. The topics covered include the re-naming of the Code, the acceptance of English as an alternative to Latin for validating diagnoses, conditions for permitting electronic publication of names, mandatory deposit of key nomenclatural information in a recognized repository for the valid publication of fungal names, the discontinuance of dual nomenclature for pleomorphic fungi, clarification of the typification of sanctioned names, and acceptability of names originally published under the zoological code. Collectively, these changes are the most fundamental to have been enacted at a single Congress since the 1950s, and herald the dawn of a new era in the practice of fungal nomenclature.